Efficiency of spearmint (Mentha spicata L.) and liquorice (Glycyrrhiza glabra L.) extracts in oxidative stability of fish oil under accelerated conditions - Uçak, Ilknur (Progress in Nutrition, 2018)
Nowadays, innumerable synthetic and naturally sourced antioxidants are used to overcome the quality problems of fish and fish products. When considering the rejection of synthetic additives by consumers, demand for the natural sources food supplements has increased. This study focuses on the potential use of spearmint (Mentha spicata L.) and liquorice (Glycyrrhiza glabra L.) extracts as natural antioxidant in fish oil during accelerated storage. Ethanolic (70%) extracts of spearmint and liquorice were prepared and synthetic antioxidant butylated hydroxytoluene (BHT) added into the fish oil in different concentrations (100, 500 and 1,000 ppm). The peroxide value (PV), thiobarbituric acid value (TBARS), para-anisidine value (p-Av) and UV-spectrum analyses of fish oil were evaluated during storage at 55oC. Throughout the the storage period the PV, TBARS value, p-Av, conjugated dienes (UV232) and conjugated trienes (UV270) values of spearmint and liquorice extracts added samples were significantly lower than the control and BHT added samples. According to results of the study, 500 and 1,000 ppm concentrations of spearmint and liquorice extracts were more effective in prevention of lipid oxidation in fish oil. The results revail that spearmint and liquorice extracts could be a natural antioxidant source for oxidative stability of fish oil. These findings can help to evaluation of liqurice and spearmint as a natural antioxidant source in fish oil industry.